Adat as Strategy for Legal Struggle and Legal Mobilization (Adat Sebagai Strategi Perjuangan dan Mobilisasi Hukum) - Arizona, Yance (The Indonesian Journal of Socio-Legal Studies, 2023)
The word "adat" has several different meanings in Indonesia. Adat can be used to describe informal dispute settlement procedures, a habit that keeps repeating itself, or a norm that develops into a code of behavior. Adat is perceived in this article as a narrative and a strategy employed by oppressed groups to fight against various forms of exclusion, particularly in relation to land grabbing for resource extraction and conservation carried out by the state and private sectors. This article will analyze the evolution and distinctions of Adat-based studies and movements in Indonesia during the colonial and national periods. Using existing secondary material from various studies on indigenous studies and movements, this article shows the differences in agendas, strategies and actors that use adat in legal discourse and legal mobilization over time. The connection between local, national, and international contexts will also be covered in this study, along with how rural communities dealing with agrarian issues have turned to adat as a strategy for legal mobilization.